A Combined Tamaru Allylation/Olefin Cross-Metathesis Approach for the Total Syntheses of (±)-Paniculidine B, (±)-Paniculidine C, and 2-Methylcarbazole - Tseng, Yi-Lun; Liang, Min-Chieh; Chen, I-Chia; Wu, Yen-Ku (Synlett, 2018)
A concise approach to the total syntheses of racemic paniculidines B and C is described. The route features a combined Tamaru allylation/olefin cross-metathesis sequence for the regiocontrolled synthesis of prenylindole intermediates. In addition, we report a transformation of the prenylated indole into 2-methylcarbazole catalyzed by sulfonic acid-functionalized silica gel.
Keywords: prenylindoles; Tamaru allylation; cross-metathesis; carbazoles; total synthesis; alkaloids